Synthesis and Characterization oF PANI/NiCo Composite - Rana, Nidhi (My University, 2009)
Films of polyaniline (PANI) and PANI/NiCo composites have been synthesized spin coating technique. The NiCo powder of particle size 10-12nm was synthesized by chloride salts of nickel and cobalt and hydrazine hydrate as reducing agent. The polyaniline was synthesized by chemical oxidative polymerization of aniline. The composite films were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and Fourier transform infra red (FTIR) and the results were compared with polyaniline films. The thermal behavior was also noted which shows the greater stability of the composite PANI/NiCo as compared to PANI.The conductivities of the thin films were also calculated. The composite shows the greater value of the conductivity. The XRD pattern of the composite possesses a peak corresponding to the plane (531), which was not present in the NiCo powders. This may be attributed to the attachment of the polymer chains along this plane. The characteristic FTIR peaks of PANI were found to shift to higher wave number in PANI/NiCo composite. These observed effects have been attributed to interaction of NiCo particles with PANI molecular chains. Films of polyaniline (PANI) and PANI/NiCo composites have been synthesized by spin coating technique. The NiCo powder of particle size 10-12nm was synthesized by chloride salts of nickel and cobalt and hydrazine hydrate as reducing agent. The polyaniline was synthesized by chemical oxidative polymerization of aniline. The composite films were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM) and Fourier transform infra red (FTIR) and the results were compared with polyaniline films. The thermal behavior was also observed which shows the greater stability of PANI/NiCo composite as compared to PANI. The conductivities of thin films were also calculated. The composite shows the greater value of the conductivity. The XRD pattern of the composite possesses a peak corresponding to the plane (531), which was not present in the NiCo powders. This may be attributed to the attachment of the polymer chains along this plane. The characteristic FTIR peaks of PANI were found to shift to higher wave number in PANI/NiCo composite. These observed effects have been attributed to interaction of NiCo particles with PANI molecular chains.
M.Tech.(Material Science and Engineering)
Keywords: PANI, NiCo